Analysis of Competency, Discipline, and Self-Efficacy on The Performance of Aviation Security Staff: Literature Review - Primadi Candra Susanto; Ni Nyoman Sawitri; Hapzi Ali; Zahara Tussoleha Ronny (Greenation International Journal of Tourism and Management, 2024)
This research aims to see the influence between variables and analyze the factors that cause personal aviation security performance. This research uses a literature review study to systematically review previous articles to see their correlation with current research. The results show that there is an influence between all independent variables on the dependent variable. This finding could be something new in qualitative research, aviation security performance can improve with competency appropriate to their field of work, work discipline while on duty, and self-efficacy at all levels, thereby creating good work achievements according to management's expectations. In human resource management research, there is no research framework like this article and the hypotheses in this research are very rarely found in previous research. Purpose – This research builds a theory of whether there is an influence between independent variables on the dependent variable. Design/methodology/approach – The method used is library research which analyzes previous articles as a literature review. Findings – There is a significant influence between variable X1 on Y, variable X2 on Y, and variable X3 on Y. Research limitations/implications – Many other factors influence performance, including remuneration, motivation, leadership style, and job satisfaction. Practical implications – The depth of this research reviews the performance of personal aviation security who are tasked with checking the luggage of passengers entering the airport area. Originality/value – Researchers have tried to look for the same research model but have not found it, there has never been previous research that discusses the influence of the independent variable on the dependent variable.